PEST Control of Molecular Stripping of NFκB from DNA Transcription Sites - Potoyan, Davit A. (J Phys Chem B, 2016)
We recently proposed a model for the IκBα-mediated molecular stripping of NFκB from transcription sites. IκBα was shown experimentally to form a transient ternary complex with DNA-bound NFκB, but the mechanism by which the IκBα accelerates dissociation of the NFκB from the DNA was unknown. In this paper we construct and compute free energy profiles for the wild type IκBα-mediated molecular stripping reaction of NFκB from DNA and compare with that for a mutant of IκBα bearing a charge-neutralized PEST. The differences in the free energy profile for stripping originate from the frustrated electrostatic interactions between the negatively charged PEST and the DNA. The PEST occupies two different conformations in the NFκB-IκBα binary complex, one of which occupies the DNA-binding cavity. Specific interactions with positively charged residues in the N-terminal domains of both p50 and p65 apparently draw the domains closer together hindering re-association of DNA. Comparison with the charge-neutralized mutant reveals that all of these functional consequences result from the negative charges in the PEST sequence of IκBα.